ANALISIS PENGARUH PENDAPATAN PEMBIAYAAN IJARAH TERHADAP PENDAPATAN TOTAL DI BAITUL MAL WATAMWIL (BMT) AN-NUR MUHAMMADIYAH CIMANGGU PERIODE 2021-2024 - Sudrajat, Bayu (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to determine the effect of ijarah financing income on total income at BMT An-Nur Muhammadiyah Cimanggu for the 2021-2024 period. This research is a field research using a descriptive-analytical method, meaning that it describes and analyzes data in the field to draw precise and accurate conclusions. The approach used is a quantitative approach. In this study the data used is secondary data in the form of financial reports per semester provided by BMT. The data collection methods are interviews, observation and documentation. The variable in this study is the independent variable in the form of ijarah financing income. While the dependent variable is the total income of BMT. The analytical tool used in this research is simple linear regression. In testing the hypothesis using the coefficient of determination, f test and t test. The results showed that the coefficient of determination (R square) or the determining coefficient was 0.999. Simultaneously, it shows that ijarah income has a significant effect on total income with a significance level of 0.000. Partially, it shows that ijarah income has a significant effect on total income with a significance level of 0.000.